The Correlation Between Stimulation, Nutritional Status and Child Development - Heri Saputro; Intan Fazrin; Eva Agustina Yalestyarini (Universitas Airlangga, 2020)
Introduction:Developmental disorder could be affected by many factors, such as stimulation and nutritional status. This study aimed to determine the correlation between stimulation, nutritional and development of children aged 3 to 6 years old.Methods: The study design was an analytic survey with cross-sectional approach. Population was parents having children aged 3 to 6, as many as 419 in Sonorejo Village, the Work Area of the UPTD Puskesmas Grogol, Kediri Regency. Sample used were 109 respondents taken by simple random sampling technique. Independent variables were stimulation and nutritional status collected using questionnaire. Dependent variable was development of children aged 3 to 6 years old, collected using observation. Data were analyzed using ordinal regression test.Results: Results showed roughly half of respondents (52, 47.7%), with good stimulation, those with normal nutritional status 80 respondents (73.4%) and having appropriate development 88 respondents (80.7%). There was an effect caused by stimulation and nutritional status for development of children aged 3 to 6 years. Results from the statistical test showed p value 0.000 for stimulation factor. This means that stimulation was a dominant factor for children's development.Conclusion: stimulation and nutritional status are very important for development of children aged 3 to 6 years old. This study suggested that parents should be more active in joining with health service centers so they can give an appropriate stimulation and increasing nutritional status for their children, so they can have optimal growth and development.